IMPLEMENTASI PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR (Pemanfaatanya Bagi Peserta Didik) - Muli Prima Aldi (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2019)
The value and benefits of the school library as a learning resource do not mean anything for teaching if its existence is not utilized optimally, so this requires the attention of students and teachers to better utilize it. To obtain maximum learning outcomes students must enhance interaction with these learning resources. Thus students should have high motivation and creativity to use the school library as a source of learning so that it becomes a positive habit in themselves. In addition through the school library students can educate themselves on an ongoing basis.